Creating and Sustaining Local Union Capabilities The Role of the National Union - Frost, Ann (Relations industrielles / Industrial Relations, 2001)
SummaryDrawing on case study evidence from the automotive, steel, and glass making industries, this article examines the role played by the national union in shaping local unions’ abilities to develop and sustain the capabilities critical to managing on-going workplace restructuring. The author presents evidence suggesting the importance of five national union characteristics. These characteristics are the breadth of the national union’s representational coverage; the extent of its education and training focus on new workplace issues; the resources it devotes to research on the implications of new workplace practices; the presence of multiple communication channels; and its structuring of local union representation.